Definition and taxonomy of interval colorectal cancers: a proposal for standardising nomenclature. Issue 8 (5th September 2014) - Sanduleanu, S; le Clercq, C M C; Dekker, E; Meijer, G A; Rabeneck, L; Rutter, M D; Valori, R; Young, G P; Schoen, R E
Abstract : Objective: Interval colorectal cancers (interval CRCs), that is, cancers occurring after a negative screening test or examination, are an important indicator of the quality and effectiveness of CRC screening and surveillance. In order to compare incidence rates of interval CRCs across screening programmes, a standardised definition is required. Our goal was to develop an internationally applicable definition and taxonomy for reporting on interval CRCs . Design: Using a modified Delphi process to achieve consensus, the Expert Working Group on interval CRC of the Colorectal Cancer Screening Committee of the World Endoscopy Organization developed a nomenclature for defining and characterising interval CRCs . Results: We define an interval CRC as a "colorectal cancer diagnosed after a screening or surveillance exam in which no cancer is detected, and before the date of the next recommended exam". Guidelines and principles for describing and reporting on interval CRCs are provided, and clinical scenarios to demonstrate the practical application of the nomenclature are presented. Conclusions: The Working Group on interval CRC of the World Endoscopy Organization endorses adoption of this standardised nomenclature. A standardised nomenclature will facilitate benchmarking and comparison of interval CRC rates across programmes and regions.